An Application of the Corporate Virtue Scale to Assess Managers’Perceptions of Ethical Behaviour in Public Organizations and Service Provision - Shindika, Emmanuel Selemani; Cheteni, Priviledge (Adam Mickiewicz University, Faculty of Philosophy, 2023)
A strong ethical culture is the key to any organization’s long-term success. The purpose of this research was to investigate the link between an organization’s ethical culture and its effect on workers’ well-being, as well as to test the construct validity of the Corporate Virtue Scale (CEV). In South Africa’s Buffalo Municipality, 277 managers from different government agencies made up the sample. The eight-factor CEV scale was validated through a confirmatory factor analysis. Employees’ stress and emotional exhaustion were linked to their views on the prevalence of an ethical culture in public agencies. The results of this study show that an organization’s ethical culture significantly affects its employees’ quality of life on the job. The CEV scale was found to have construct validity, proving its reliability and validity in practice. The government is urged to prioritize the streamlining of regulations and processes that foster an ethical culture in public institutions.
Keywords: CEV model; culture; ethical; public servants; organisation